The role of interventional radiology in the treatment of breast tumors - Jana Bebek; Nikolina Novak; Marina Dasović; Eugen Divjak; Gordana Ivanac (Libri Oncologici, 2024)
Radiological interventional procedures are minimally invasive techniques that use imaging guidance for the diagnosis and treatment of breast pathologies. These procedures involve various ablation methods that are used to destroy tumors by applying high or low temperatures. This group includes radiofrequency ablation (RFA), microwave ablation (MWA), highintensity focused ultrasound (HIFU), laser-induced thermotherapy (LITT), and cryoablation. The main difference between them is the energy source they use. The goal of these ablative techniques is to destroy or decrease the size of unwanted lesions while using precise imaging guidance for monitoring. Compared to traditional surgery, interventional procedures have several benefits: being less invasive, having fewer complications, reducing hospital stays, and providing better cosmetic results. However, more research is needed to compare these radiological procedures and assess their long term effectiveness and safety.